The logic of organization - Kuhn, Alfred (Jossey-Bass, 1982)
This exploration of organizational theory focuses on the genesis of organizations and the conditions for their continued existence. Drawing upon the classic theories of Marx, Weber and Michels as well as more contemporary developments in organizational theory, Abrahamsson presents his unique theory - that organizations are deliberately designed social structures which have been established by a certain person, group or class in order to implement certain goals.